Symmetry correlations between crystallographic and photoluminescence study of ternary β-diketone europium(iii) based complexes using 1, 10-phenanthroline as the ancillary ligand. Issue 42 (16th October 2019) - Alexander, Orbett T.; Kroon, Robin E.; Brink, Alice; Visser, Hendrik G.
Abstract : This work entails deep red emitting Eu III based complexes with a variety of ternary β-diketonate ligands and 1, 10-phenanthroline as the ancillary ligand in the system. Abstract : This work entails deep red emitting Eu III based complexes with a variety of ternary β-diketonate ligands and 1, 10-phenanthroline as the ancillary ligand in the system. The solid state structure and spectroscopic analysis has been outlaid in terms of photoluminescence and crystallography. A luminescence quantum efficiency of 50% was obtained for the [ tris-(4, 4, 4-trifluoro-1-chlorophenyl-butanedione)mono-(1, 10-phenanthroline)europium(iii )] complexes. Moreover, complexes [tris-(2, 2, 6, 6-tetramethyl-heptanedione)mono-(1, 10-phenanthroline) europium(iii )] and [hexa-(benzyl carboxylic acid) bis-(1, 10-phenanthroline)di-europium(iii )]-μ-[κ 2 -O, O′-(benzyl carboxylic acid)]2 were found to also have quantum yields of 9% and 28% with respective sensitization efficiencies of 85%, 15% and 58%. These results were articulated with crystallographic details pertaining to the nature of coordination and the effect of steric and electronic properties thereof which somewhat impacts the Eu–N bond distances. A symmetry correlation was drawn between the crystallographic data and the photoluminescence data.